The effect of clinical guidelines on the utilisation of radiographs in chiropractic clinics in Denmark - an interrupted time series analysis - Pernille Schaldemose Reibke; Henriette Godskesen; Rikke Krüger Jensen; Simon D French; André Bussières; Henrik Wulff Christensen; Tue Secher Jensen (Chiropractic & Manual Therapies, 2023)
Abstract Background In Denmark, chiropractors have a statutory right to use radiography and the government-funded national Health Insurance provides partial reimbursement. Danish National Clinical Guidelines recommends against routine use of imaging for uncomplicated spinal pain; however, it is not clear if clinical imaging guidelines recommendations have had an effect on the utilisation of spinal radiography. This study aimed to describe the utilisation rate of radiographs in Danish chiropractic clinics in the period from 2010 to 2020 and to assess the impact of clinical guidelines and policy changes on the utilisation of radiographs in Danish chiropractic clinics. Methods Anonymised data from January 1st, 2010, to December 31st, 2020, were extracted from the Danish Regions register on health contacts in primary care. Data consisted of the total number of patients consulting one of 254 chiropractic clinics and the total number of patients having or being referred for radiography. Data were used to investigate the radiography utilisation per month from 2010 to 2020. An ‘interrupted time series’ analysis was conducted to determine if two interventions, the dissemination of 1) Danish clinical imaging guidelines recommendations and policy changes related to referral for advanced imaging for chiropractors in 2013 and 2) four Danish clinical guidelines recommendations in 2016, were associated with an immediate change in the level and/or slope of radiography utilisation. Results In total, 336,128 unique patients consulted a chiropractor in 2010 of which 55,449 (15.4%) had radiography. In 2020, the number of patients consulting a chiropractor had increased to 366,732 of which 29,244 (8.0%) had radiography. The pre-intervention utilisation decreased by two radiographs per 10,000 patients per month. Little absolute change, but still statistically significant for Intervention 1, in the utilisation was found after the dissemination of the clinical guidelines and policy changes in 2013 or 2016. Conclusions The proportion of Danish chiropractic patients undergoing radiography was halved in the period from 2010 to 2020. However, the dissemination of clinical imaging guidelines recommendations and policy changes related to referrals for advanced imaging showed little meaningful change in the monthly utilisation of radiographs in the same period.